The Gothic ‘Skeireins’ in the Greek Original - Friedrichsen, George Washington Salisburgy (New Testament studies, 1961)
The present work is intended to furnish a further contribution to the much debated, yet still unsettled question as to whether the Skeireins was the original work of a Gothic commentator writing in his vernacular, or whether it was translated into Gothic from a commentary in Greek or Latin.The not inconsiderable portions of the N.T. in Gothic bear witness to the manner in which the translators followed the Greek original word by word, and often syllable by syllable. Their literalism extends to the order, the vocabulary, the constructions and often to exact calques of the Greek words.